2019
DOI: 10.1021/acs.est.9b02400
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Leachates from UV-Weathered Microplastic in Cell-Based Bioassays

Abstract: Standard ecotoxicological testing of microplastic does not provide insight into the influence that environmental weathering by, e.g., UV light has on related effects. In this study, we leached chemicals from plastic into artificial seawater during simulated UV-induced weathering. We tested largely additive-free preproduction polyethylene, polyethylene terephthalate, polypropylene, and polystyrene and two types of plastic obtained from electronic equipment as positive controls. Leachates were concentrated by so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
69
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 66 publications
10
69
0
1
Order By: Relevance
“…The results of the univariate and multivariate analyses suggest that light conditions influence the interaction between photosynthesizing MPB, infaunal burrowing, nutrient pools and microfibers in the sediment. UV weathering is an important mechanism by which plastics degrade in the natural environment 111 and previous studies have observed oxidative stress in cell-based bioassays due to the leachates from weathered polyethylene terephthalate (PET) 112 . UV weathering of the plastic fibers can result in the liberation of chemicals from the plastic into the surrounding environment 112 .…”
Section: Resultsmentioning
confidence: 99%
“…The results of the univariate and multivariate analyses suggest that light conditions influence the interaction between photosynthesizing MPB, infaunal burrowing, nutrient pools and microfibers in the sediment. UV weathering is an important mechanism by which plastics degrade in the natural environment 111 and previous studies have observed oxidative stress in cell-based bioassays due to the leachates from weathered polyethylene terephthalate (PET) 112 . UV weathering of the plastic fibers can result in the liberation of chemicals from the plastic into the surrounding environment 112 .…”
Section: Resultsmentioning
confidence: 99%
“…Rochman et al (2014) have previously observed that naturally weathered PE has more endocrine disruptive effects compared to virgin PE. Gewert et al (2018) studied polymer degradation products released to water under UV light exposure, using the same Goodfellow plastic pellets used in this study, and identified mostly oligomeric dicarboxylic acids; but these only partially explained toxicity observed in cell-based bioassays (Rummel et al, 2019). The increased toxicity observed for some old materials in this study might be caused by prior leaching of additives that are UV stabilizers.…”
Section: Effects Of Weathering On Leachate Toxicitymentioning
confidence: 86%
“…According to the distributor, these pellets contain few additives at low levels. These same pellets have been used in toxicity screening experiments using cell-based bioassays (Rummel et al, 2019). A fraction of these plastic pellets was deployed in floating mesocosms in the Oslo fjord near the town of Drøback for seven months (April-October 2017).…”
Section: Methodsmentioning
confidence: 99%
“…This provides a vector for the transportation of these pollutants by particles floating in seawater over long distances. After the ingestion by different animals, such pollutants can be leached from the particles and enter animal tissues, where they can disrupt normal biochemical processes in the cells [55]. Microplastic particles also represent a source of hormone‐disrupting compounds themselves due to additives that are added during the manufacturing process to achieve particular characteristics.…”
Section: Effect On Marine Organismsmentioning
confidence: 99%